Punishment, globalization and migration control: ‘Get them the hell out of here’ - Bosworth, Mary (Punishment & society, 2018)
This article considers the future of punishment in a world shaped by competing and reinforcing forces of globalization and nationalism. In it, we call for a wider conversation about the growing interdependence between criminal justice and migration control and of its implications for many of the key concepts and approaches within the field of punishment and society. The article examines the renewed salience of defending borders and drawing boundaries between members and non-members, as well as the shifting focus of penal power from issues of imprisonment and morality, towards questions of immobilization and expulsion from the polity. By doing so, it also addresses the gaps in the existing theories and narratives about penality, which fail to take properly into account the implications of global connectivity, while overlooking enduring matters of racial and class inequity. Finally, the article points out how the progressive destabilization of citizenship and the precarity of membership and belonging are inimically linked to increasingly potent exhortations of penal power that affect us all.